Tantinho, memória em verde e rosa: estudo do processo de construção de uma memória da Favela da Mangueira - Constant, Flávia Martins (2007)
The present work proposes a reflection on memories construction, based on the case study Tantinho, memória em verde e rosa CD. The main methodology was oral history, looking for use personal narratives as a source for inquiry memories construction. The research universe is composed of the most important social agents involved in the construction of this memory, what included Tantinho and other 'samba' composers from Mangueira slum, as well as other people involved in the production of these CD. Eight people have been interviewed, totalizing more than 12 hours of interview. Considering the contemporary movement of memories construction of Rio de Janeiro´s slums and the relevance of Mangueira slum in this context, we find these CD study case important to understand more about this process and, mainly, about the relationships that are necessary for a memory construction.